2017
DOI: 10.2147/rru.s128499
|View full text |Cite
|
Sign up to set email alerts
|

Prostate MRI prior to radical prostatectomy: effects on nerve sparing and pathological margin status

Abstract: ObjectivesThe aim of this study was to assess the positive surgical margin (PSM) and nerve sparing (NS) rates in patients who underwent prostate MRI (pMRI) prior to radical prostatectomy (RP) and compare them with matched, nonimaged control RP patients.MethodsWe identified 204 men who underwent preoperative pelvic MRI (pelMRI), of whom 176 (86.3%) underwent pMRIs, within 60 days of RP, and compared them (1:1) with a nonim-aged control group matched by surgeon, age, race, body mass index (BMI), prostate-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Our meta-analysis has shown that in those who had preoperative MRI rate of PSMs is no different irrespectively of the direction of surgical technique adaptation (Fig 9). In matched control study, despite the difference in crude numbers, PSM rates in pelvic MRI and non-MRI groups were similar (13.7% vs 19.3%) [21]. This relation was also observed at subgroup analysis in patients with T1c PCa (11.0% vs 18.1%) and more advanced disease as well (21.4% vs 25.0%) [21].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our meta-analysis has shown that in those who had preoperative MRI rate of PSMs is no different irrespectively of the direction of surgical technique adaptation (Fig 9). In matched control study, despite the difference in crude numbers, PSM rates in pelvic MRI and non-MRI groups were similar (13.7% vs 19.3%) [21]. This relation was also observed at subgroup analysis in patients with T1c PCa (11.0% vs 18.1%) and more advanced disease as well (21.4% vs 25.0%) [21].…”
Section: Discussionmentioning
confidence: 90%
“…These diversities may reflect various accommodation of MRI images in different studies. In the trial by Durskin et al, NVB-sparing rates between MRI and non-MRI group were similar despite suggestion of non-focal EPE in pelvic MRI in selected cases [21]. Therefore, despite fairly high diagnostic accuracy these observations indicate, that MRI before RP is being adopted with great caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%. 71 Similarly, Druskin et al 70 showed that the use of preoperative MRI in patients undergoing RP resulted in a 5.6% decrease in the PSM rate.…”
Section: Mrimentioning
confidence: 96%
“…Several authors studied the clinical value of preoperative MRI on surgical planning and PSM rates showing that it may influence the surgical decision in 26% to 59% of patients. [65][66][67][68][69][70] Recently, Kozikowski et al 71 reported, in their systematic review and meta-analysis, that MRI modified the NVB dissection on 1 or both sides in 35% of patients, of which 63% performed a more aggressive resection of the bundle and 37% had more preservation of the bundle. Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%.…”
Section: Mrimentioning
confidence: 99%